Breast Tenderness after Initiation of Conjugated Equine Estrogens and Mammographic Density Change - Crandall, Carolyn J. (2011)
BACKGROUND: We examined the association between new-onset breast tenderness and change in mammographic density after initiation of conjugated equine estrogens (CEE). METHODS: We analyzed baseline, year 1, and year 2 data from 695 participants of the Women's Health Initiative Estrogen + Progestin (daily CEE 0.625 mg + medroxyprogesterone acetate 2.5 mg [MPA] or placebo) and Estrogen-Alone (CEE 0.625 mg or placebo) trials who participated in the Mammogram Density Ancillary Study. Using multivariable repeated measures models, we analyzed the association between new-onset breast tenderness (i.e. absence of baseline tenderness and presence of tenderness at year 1 follow-up) and change from baseline in percent mammographic density. RESULTS: Active therapy increased the odds of new-onset breast tenderness (CEE + MPA vs. placebo risk ratio [RR] 3.01, 95% confidence interval [95% CI] 1.96-4.62; CEE vs. placebo RR 1.70, 95% CI 1.14-2.53). Among women assigned to CEE + MPA, mean increase in mammographic density was greater among participants reporting new-onset of breast tenderness than among participants without new-onset breast tenderness (11.3% vs. 3.9% at year 1, 9.4% vs. 3.2% at year 2, P < 0.001). Among women assigned to CEE alone, increase in mammographic density at year 1 follow-up was not significantly different in women with new-onset breast tenderness compared to women without new-onset breast tenderness (2.4% vs. 0.6% at year 1, 2.2% vs. 1.0% at year 2, P = 0.30). CONCLUSIONS: The new-onset of breast tenderness after initiation of CEE + MPA, but not CEE alone, is associated with greater increases in mammographic density.